The concept of citizenship - The study of the theory - اسامة عبد علي خلف (College of Education for Women, 2019)
With the growth of democratic thought in our country, widened the trading term citizenship to the magnitude of the meanings of participation in political life, economic, social and cultural rights, as the recipe ( citizen ) does not mean only affiliation to the homeland and link him as a child , but is as such an actor in various fields has his being independent , and own convictions and the right to freely express his views and personal choices and play a positive role in public life . Do not correct the democratic structure of any state without the manifestation of the spirit of citizenship in the relations of each individual citizen to state institutions. The current research aims to Pfhom definition of citizenship and the historical origins and show the most prominent elements of citizenship and political dimensions, legal and